Implementation of Aquatic Environmental Monitoring Technology in Solar-Powered Seaweed Cultivation to Optimize the Productivity of the Masempo Dalle Fishermen Group, Pinrang Regency - Intan Sari Areni; Ashadi Amir; Nur An-Nisa Putry Mangarengi (Faculty of Engineering UNHAS, 2025)
Watang Suppa Village, Suppa Sub-district, Pinrang Regency has great potential for seaweed cultivation; however, the Masempo Dalle Fishermen Group still faces several challenges, particularly the limitation in monitoring water environmental conditions in real-time. Conventional methods based on visual observation and empirical experience result in low accuracy in assessing cultivation site suitability, leading to fluctuating yields and economic losses. This Community Service Program aims to enhance seaweed farming productivity through the implementation of an Internet of Things (IoT)-based water quality monitoring system powered by solar energy, while also improving fishermen’s knowledge and skills in technology utilization. The implementation method consisted of socialization, training, two phases of technology trials, and monitoring and evaluation. The results indicated a significant increase in fishermen’s knowledge, such as water quality parameter understanding improving from 42% to 78%, readiness to adopt technology from 40% to 76%, and basic IoT comprehension from 35% to 75%. Technical capabilities also improved, with the ability to read sensor data rising from 38% to 78%, device installation understanding from 32% to 70%, and maintenance skills from 30% to 68%. The technology trials successfully provided more accurate water quality data and enabled fishermen to monitor cultivation sites in real-time. This program is expected to serve as an initial step toward building technological independence in coastal communities and promoting sustainable aquaculture practices.